PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GI BERBANTUAN SPACE 4D+ AR PLAYING CARD UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK SMP NEGERI 4 PEKANBARU PADA MATERI BUMI DAN TATA SURYA - Dean Irvanda Tri Kharisma; Muhammad Nasir; Fakhruddin Z (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
This article aims to improve students' cognitive learning outcomes by applying the group investigation cooperative learning model assisted by space 4d+ augmented reality playing cards and to test whether there are differences in the cognitive learning outcomes of students who apply the group investigation cooperative learning model assisted by space 4d+ augmented reality playing cards with students who do not apply the group investigation cooperative learning model assisted by space 4d+ augmented reality playing cards. The target is class VII students at SMP Negeri 4 Pekanbaru for the 2022/2023 academic year, which consists of 10 classes and a total of 392 students. Data collection techniques were obtained through posttests. The results of the descriptive analysis of students' cognitive learning outcomes showed that the average difference between the experimental class and the control class was positive at 18.6. space 4d+ augmented reality playing card with classes using conventional methods with a confidence level of 95%